2010 IEEE International Conference on Acoustics, Speech and Signal Processing 2010
DOI: 10.1109/icassp.2010.5495491
|View full text |Cite
|
Sign up to set email alerts
|

Anti-forensics of JPEG compression

Abstract: The widespread availability of photo editing software has made it easy to create visually convincing digital image forgeries. To address this problem, there has been much recent work in the eld of digital image forensics. There has been little work, however, in the eld of anti-forensics, which seeks to develop a set of techniques designed to fool current forensic methodologies. In this work, we present a technique for disguising an image's JPEG compression history. An image's JPEG compression history can be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 8 publications
0
82
0
Order By: Relevance
“…For this reason, technique [87] cleans blocking artifacts by applying first a median filter and then adding low-power white noise to the image. It is shown that this operation outperforms existing de-blocking techniques when coupled to method [86] for compression hiding. "Polished" images are then recompressed with quantization tables typical of other cameras, and their quantization matrices estimated through method [70].…”
Section: Image Source Counterfeitingmentioning
confidence: 99%
See 3 more Smart Citations
“…For this reason, technique [87] cleans blocking artifacts by applying first a median filter and then adding low-power white noise to the image. It is shown that this operation outperforms existing de-blocking techniques when coupled to method [86] for compression hiding. "Polished" images are then recompressed with quantization tables typical of other cameras, and their quantization matrices estimated through method [70].…”
Section: Image Source Counterfeitingmentioning
confidence: 99%
“…A different method for counterfeiting image source fingerprints is proposed in [87], and is based on the manipulation of JPEG artifacts. The authors present a technique complimentary to [86] for the suppression of traces of compression and then re-forge the image by compressing it with a different quantization table, e.g. characteristic of another device.…”
Section: Image Source Counterfeitingmentioning
confidence: 99%
See 2 more Smart Citations
“…The first attempts to make JPEG footprints forensically undetectable on the basis of DCT artifacts are the techniques introduced by stamm et al in their papers in [17,18]. In the first paper, quantisation gaps in the DCT histogram are reduced by spreading the coefficients with an additive noise called anti-forensic dither.…”
Section: Jpeg Compression Anti-forensicsmentioning
confidence: 99%